APPLICATION OF PERFORMANCE-BASED BUDGET ON PERFORMANCE MOTIVATION OF ENVIRONMENTAL SERVICE AND FORESTRY BENGKULU PROVINCE - Putra, Iswidana Utama; Susanti, Melly; Wijaya, Ermy (STIE Kusuma Negara, 2020)
This study aims to empirically examine the relationship between the application of performance-based budgeting to work motivation in government agencies in the Department of Environment and Forestry of Bengkulu Province. The independent variable is the application of performance-based budgeting using indicators of budget transparency and motivation, budget discipline, budget equity, budget efficiency and effectiveness, while the dependent variable is the performance motivation of government agencies with indicators of motives, expectations and incentives. By using purposive sampling method in sampling and data collection methods by distributing questionnaires to 39 respondents, as for the method in analyzing data using the Spearman Rank Test and hypothesis testing. The results of this study indicate that the three independent variables namely the implementation of performance-based budgeting with indicators of budget transparency and motivation, budget discipline, budget equity, budget efficiency and effectiveness have a positive effect on the work motivation of government agencies.